PROBLEMS OF DIGITALIZATION OF FINANCIAL POLICY IN A MARKET ECONOMY - Turayev Alijon Akmal o'g'li; Qurbanov Azimjon Xasanovich; Ibragimov Azamat Sobir o'g'li (Лучшие интеллектуальные исследования, 2023)
Abstract: The article explores current problems associated with the digitalization of financial policy in a market economy. The authors analyze the impact of digital technologies on public financial management, identify challenges that arise in the process of digital transformation of the financial sector and offer recommendations for solving them.